Antimony and arsenic migration in a heterogeneous subsurface at an abandoned antimony smelter under rainfall - Li, Chao; Ran, Yiyuan; Wu, Pan; Liu, Peng; Yang, Boyi; Gu, Xueyuan; Zhao, Ping; Liu, Shirong; Song, Lei; Liu, Yuhui; Liu, Yizhang; Ning, Zengping; et al. (Journal of hazardous materials, 2024)
While antimony (Sb) and arsenic (As) co-contamination in subsurface soil systems due to the legacy of Sb smelting wastes has been documented, the role of inherent heterogeneity on pollutant migration is largely overlooked. Herein this study investigated Sb and As migration in a slag impacted, vertically stratified subsurface at an abandoned Sb smelter. A 2-dimensional flume was assembled as a lab-scale analogue of the site and subject to rainfall and stop-rain events. Reactive transport modeling was then performed by matching the experimental observations to verify the key factors and processes controlling pollutant migration. Results showed that rainfall caused Sb and As release from the shallow slag layer and promoted their downward movement. Nevertheless, the less permeable deeper layers limited physical flow and transport, which led to Sb and As accumulation at the interface. The re-adsorption of Sb and As onto iron oxides in the deeper, more acidic layers further retarded their migration. Because of the large difference between Sb and As concentrations, Sb re-adsorption was much less effective, which led to higher mobility. Our findings overall highlight the necessity of understanding the degree and impacts of physicochemical heterogeneity for risk exposure assessment and remediation of abandoned Sb smelting sites. [Display omitted] •Migration of Sb and As in a smelting impacted, stratified subsurface was studied.•The heterogeneity in permeability caused Sb and As accumulation at the interface.•Sb and As re-adsorption in the deeper, more acidic layers retarded their migration.•The Sb mobility was high due to high Sb solid content and ineffective re-adsorption.